PENGARUH PENGALAMAN PRAKTIK KERJA INDUSTRI DAN MOTIVASI MEMASUKI DUNIA KERJA TERHADAP KESIAPAN KERJA PESERTA DIDIK SMK KRISTEN 1 SURAKARTA TAHUN ANGKATAN 2017/2018 - -, Deas Bella Rosara -; -, Harini -; -, Jonet Ariyanto Nugroho - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
The purpose of this research 1) to find out  the influence of experince of  indsutrial work practices and motivation to enter the work world to the work readiness of students of SMK Kristen 1 Surakarta  academic year 2017/2018, 2) to find out  the influence of  experience of industrial work practices to the work readiness of students of SMK Kristen 1 Surakarta, 3) to find out the influence of motivation to enter the work world to the work readiness of students of SMK Kristen 1 Surakarta. The population is students of SMK Kristen 1 Surakarta. The sampling technique is Proportionate Stratified Random Sampling. The sample size is 150 respondents. Data collection techniques are interviews, questionnaires and documentation. Data analysis technique is multiple linear regression.             The results showed that multiple regression equation of Y = 31.821 + 0.497 X1 + 0.421 X2.  Based on the result, can be concluded that (1) experience of industrial work practices and motivation to enter the work world simultainly influence to the students work readiness which shown with probability value 0.000, (2) experience industrial work practices positively and significantly influence to the work readiness with probability value 0,000, (3) the motivation to enter the work world positively and significantly influences to the work readiness with probability 0,000. Value of R square is 60,5%. It shows that 60,5% readiness of work is influenced by experience of industrial work practice and motivation to enter work world, while 39,5% influenced by other factors not explained in research.